Peran Manajemen Resiko Dalam Penjaminan Keberlangsungan Usaha Kecil dan Menengah (UKM) Pada Usaha Laundry - N, Nuragustin; Adriansyah, Ahmad Alvin; Fadlan, Muhammad; Lubis, Farah Ananda; A, Arsyadona (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Laundry businesses, as part of SMEs, often face challenges such as machine breakdowns, service errors, and fluctuations in customer demand, which can disrupt operations and threaten business sustainability. This study aims to examine how risk management can help laundry businesses address these issues. Using a qualitative approach through literature review, the study identifies essential steps such as employee training, regular machine maintenance, and service diversification to mitigate risks. The findings reveal that effective risk management enhances customer trust, maintains service quality, and strengthens business competitiveness. Furthermore, adopting modern technology makes laundry businesses more efficient and resilient in facing market competition. These findings provide practical guidance for laundry business owners to ensure the sustainability of their businesses.